2020
DOI: 10.3390/en13102431
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Compressed Gas Energy Storage Density Using CO2–N2 Gas Mixture

Abstract: This paper demonstrates a new method by which the energy storage density of compressed air systems is increased by 56.8% by changing the composition of the compressed gas to include a condensable component. A higher storage density of 7.33 MJ/m3 is possible using a mixture of 88% CO2 and 12% N2 compared to 4.67 MJ/m3 using pure N2. This ratio of gases representing an optimum mixture was determined through computer simulations that considered a variety of different proportions from pure CO2 to pure N2. The comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The storage needs to be sized to provide a predetermined power rating for on-demand energy, as illustrated in [71,83,171] for a given autonomy and not long-term storage like utility-scale types. The optimization of CAES to meet requirements of behindthe-meter applications will require the problems of low RTE and energy density values to be solved [177]. Pressure and speed controllers for load governors can be replaced or better improved with power electronic ancillaries for effective power and efficiency tracking [87].…”
Section: Behind-the-meter Applicationmentioning
confidence: 99%
“…The storage needs to be sized to provide a predetermined power rating for on-demand energy, as illustrated in [71,83,171] for a given autonomy and not long-term storage like utility-scale types. The optimization of CAES to meet requirements of behindthe-meter applications will require the problems of low RTE and energy density values to be solved [177]. Pressure and speed controllers for load governors can be replaced or better improved with power electronic ancillaries for effective power and efficiency tracking [87].…”
Section: Behind-the-meter Applicationmentioning
confidence: 99%
“…This loss of available energy negatively affects the economics of generation at such Figure 10. Within the same pressure limits, a non-condensable gas system (a) will utilize less volume than a system with condensable gas (b) (Abuheiba et al 2020)…”
Section: Executive Summarymentioning
confidence: 99%
“…Detailed model and simulation study of the impact of using condensing fluid in GLIDES on its energy density is reported in (Abuheiba et al 2020). A proof-of-concept prototype of the condensing GLIDES configuration was built and evaluated in the laboratory.…”
Section: Condensing Glidesmentioning
confidence: 99%
See 1 more Smart Citation